New product development with the innovative biomolecular sublingual immunotherapy formulations for the management of allergic rhinitis - Frati F (Dove Medical Press, 2014)
Franco Frati,1 Lorenzo Cecchi,2,3 Enrico Scala,4 Erminia Ridolo,5 Ilaria Dell'Albani,1 Eleni Makrì,6 Giovanni Pajno,7 Cristoforo Incorvaia6 1Medical and Scientific Department, Stallergenes, Milan, Italy; 2Interdepartmental Centre of Bioclimatology, University of Florence, Florence, Italy; 3Allergy and Clinical Immunology Section, Azienda Sanitaria di Prato, Prato, Italy; 4Experimental Allergy Unit, IDI-IRCCS, Rome, Italy; 5Department of Clinical and Experimental Medicine, University of Parma, Parma, Italy; 6Allergy/Pulmonary Rehabilitation, ICP Hospital, Milan, Italy; 7Department of Pediatrics, Allergy Unit, University of Messina, Messina, Italy Abstract: The molecular allergy technique, currently defined as component-resolved diagnosis, significantly improved the diagnosis of allergy, allowing for differentiation between molecules actually responsible for clinical symptoms (genuine sensitizers) and those simply cross-reacting or shared by several sources (panallergens), thus influencing the appropriate management of a patient's allergy. This also concerns allergen immunotherapy (AIT), which may be prescribed more precisely based on the component-resolved diagnosis results. However, the advance in diagnosis needs to be mirrored in AIT. According to consensus documents and to expectations of specialists, therapy should be based on standardized extracts containing measured amounts of the clinically relevant molecules, ie, the major allergens. The new generation of extracts for sublingual immunotherapy fulfills these requirements and are thus defined as biomolecular (BM). BM refers to natural extracts with a defined content of major allergens in micrograms. All Staloral BM products are indicated for the treatment of allergic rhinitis with or without asthma. The effectiveness of AIT is related to its ability to modify the immunological response of allergic subjects. The 5-grass and house dust mite extracts were evaluated addressing the T helper 1, T helper 2, and T helper 3 cells by polymerase chain reaction array on mRNA extracted from Waldeyer's ring tissue (adenoids). Sublingual immunotherapy with a defined content of major allergens in micrograms induced a strong downregulation of genes involved in T helper 2 and T helper 1 activation and function, allowing the definition of the immunologic effect as "bio-homeostatic". This clinical and immunological model must be implemented with respect to other allergens, thus expanding the application of a treatment with a unique disease-modifying capacity. Keywords: allergen immunotherapy, allergy, component resolved diagnosis, major allergens, allergen molecules